Synthesis of molecularly imprinted polymers of vanillic acid and extraction of vanillic acid from spiked blood serum - Showkat Ahmad, Bhawani; Salma, Bakhtiar; Rachel Marcella, Roland; Syed Rizwan, Shafqat; Mohamad Nasir, Mohamad Ibrahim (Open Science Publishers, 2020)
Vanillic acid (4-hydroxy-3-methoxybenzoic acid) is a phenolic acid found in many plant extracts. It is used as a flavoring and scent agent and produces a pleasant, creamy odor. It is widely used in many applications for therapeutic purposes to flavoring agent. Molecularly imprinted polymers of vanillic acid were synthesized by precipitation polymerization with a noncovalent approach for the extraction from blood serum. Three different imprinted polymers have been synthesized with varying molar ratio of monomer. The synthesized polymer particles were characterized using Fourier-transform infrared spectroscopy and scanning electron microscopy. The extraction efficiency of highly selected imprinted polymer of vanillic acid from spiked blood serum was about 80%.